Emergency Department Care in the Postpartum Period: California Births, 2009 to 2011. Issue 1 (March 2018) - Batra, P.; Fridman, M.; Leng, M.; Gregory, K.D.
Abstract : ( Obstet Gynecol . 2017;130(5):1073–1081) Studies have estimated that up to 25% of women visit the emergency department (ED) during the postpartum period. However, despite this high volume, postpartum ED utilization data are omitted from national reports. As there has been a shift toward early postpartum discharge from the hospital, the present study described postpartum ED use in a population-based sample from California as well as associated factors for ED use. The primary outcome was odds of an ED visit within 90 days of discharge. Secondary outcomes included high utilization (≥3 visits within 90 d) and inpatient admission from the ED.